Differentiated Instruction Scenario on Physics Learning: Reflection of Readiness and Future Implementation - Putra, G. S.; Pribadi, A.; Zakiyah, S. (Jurnal Pendidikan IPA Indonesia, 2023)
This study has successfully constructed the scenario of differentiated instruction (DI) on physics learning as a reflection of readiness and future implementation through undergraduate students’ beliefs. Differentiated instruction (DI) is an approach that enables teachers to plan strategically to meet the needs of every student. However, differentiated instruction in physics may or may not challenge its users in reality as it depends on beliefs and views about the nature of science, instruction, and pedagogical content knowledge. This quantitative-qualitative study involved 56 undergraduate students and consisted of three main stages: preliminary, analysis, and rendition. In the first and second stages, we found a strong negative correlation between the proportion of mathematics-conceptual knowledge of the topics and the possibility of implementing differentiated instruction (r =-0,576). Meanwhile, belief in self-proficiency is directly proportional to the DI implementation possibility (r = 0.828). In conclusion, we created two scenarios based on analysis, representing the current reality of how DI will be implemented and future implementation expectations. Moreover, this research strengthens the theory that beliefs influence the possibility of using differentiated instruction. We suggest a demand for an effective introduction to differentiation instruction during science teacher preparation programs and leading professional learning that may support the development of undergraduate students at the beginning of their careers.